Farming Practices And Livelihood Status Of Non-Saline And Saline Households In Southern Bangladesh - Uddin, MT; Erskine, W; Dhar, AR; Shishir, MI; Neogi, MG (SAARC Journal of Agriculture, 2020)
The study examined the farming practices and livelihood status of farm households in seven districts of Southern Bangladesh. Majority of the farmers in non-saline and saline areas followed the cropping pattern of Fallow – Aman rice – Pulses and Fallow – Aman rice – Fallow, respectively. Cropping intensity was higher in non-saline areas (220.0%) compared to saline areas (101.7%). Profitability of major crops was much higher in non-saline areas compared to saline areas. Based on the poverty indicators, the proportion of deprived households was 41.7 and 56.0% in non-saline and saline areas, respectively. The study recommended that in saline areas, rain water reservoirs should be developed in cooperative way and availability of electricity use should be facilitated to use light irrigation pumps in the crop field from the nearest fresh water reservoir. In addition, canal reform should be done and leasing arrangement of water canals should be stopped to get farmers’ access for irrigation purpose. Moreover, salt-tolerant and short duration pulse and wheat should be introduced in order to improve livelihood of saline farm households in Bangladesh. SAARC J. Agri., 17(2): 227-238 (2019)